2007
DOI: 10.1183/09031936.00024707
|View full text |Cite
|
Sign up to set email alerts
|

Is air travel safe for those with lung disease?

Abstract: Airlines commonly report respiratory in-flight emergencies; flight outcomes have not been examined prospectively in large numbers of respiratory patients. The current authors conducted a prospective, observational study of flight outcomes in this group.UK respiratory specialists were invited to recruit patients planning air travel. Centres undertook their usual pre-flight assessment. Within 2 weeks of returning, patients completed a questionnaire documenting symptoms, in-flight oxygen use and unscheduled healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 25 publications
4
56
1
4
Order By: Relevance
“…The greater desaturation during LFs in healthy subjects is consistent with the data of COKER et al [1], who reported worsening symptoms mainly in patients in whom average flight duration was 7.6 h. As intermittent hypoxia is an effective stimulus for evoking cardiorespiratory responses, repetitive 4% desaturations (an take-off, lunch, lavatory visit and landing. The baseline Sa,O2 was 98%; after take-off it dropped to 95% ( # ).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The greater desaturation during LFs in healthy subjects is consistent with the data of COKER et al [1], who reported worsening symptoms mainly in patients in whom average flight duration was 7.6 h. As intermittent hypoxia is an effective stimulus for evoking cardiorespiratory responses, repetitive 4% desaturations (an take-off, lunch, lavatory visit and landing. The baseline Sa,O2 was 98%; after take-off it dropped to 95% ( # ).…”
supporting
confidence: 80%
“…MCGRATH et al [1] recently reported the case of a middle-aged Caucasian female with a diagnosis of diffuse panbronchiolitis (DPB) and highlighted the difficulties of securing such a diagnosis in populations in which it is rarely described, i.e. those of Western/non-Asian origin.…”
Section: Diffuse Panbronchiolitismentioning
confidence: 99%
“…The decreased oxygen saturation may exacerbate coexisting medical conditions, such as coronary heart disease, and may also be related to the development of respiratory distress during or after the flight [1][2][3]11]. Respiratory symptoms during air travel are reported by approximately one out of five patients with COPD [8,17,18], and the development of severe hypoxaemia is well documented, both during real and simulated flights [1,3,15,[19][20][21]. The association between in-flight respiratory symptoms and hypoxaemia has, however, not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…She also discussed the UK Flight Outcomes Study, with particular reference to healthcare requirements following travel, including acute hospitalisation, antibiotic and corticosteroid usage as well as the under-appreciated deleterious effects of flight on patients with interstitial lung disease. 1 The forthcoming British Thoracic Society (BTS) recommendations on air travel and lung disease aim to update those from 2004, and are likely to include revisions such as a shortened, one-week timescale post-resolution of spontaneous pneumothorax before a commercial flight, as opposed to the previously widely accepted six-week interval.…”
Section: Session 1 Challenges In the Clinicmentioning
confidence: 99%